PENAMBAHAN LARUTAN BAWANG MERAH (Allium cepa L.) DAN AIR KELAPA (Cocos nucifera L.) SEBAGAI FITOHORMON ALAMI PADA PERTUMBUHAN TANAMAN TEBU (Sacchanum officinarum L.) SEBAGAI SUMBER BELAJAR BIOLOGI - Dewi Kurniawati; HRA Mulyani; Rasuane Noor (Bioedukasi Jurnal Pendidikan Biologi, 2020)
This study aims to 1) to see the effect of natural phytohormones in onions and coconut water on the growth of sugarcane, 2) To see the effect of giving natural phytohormones to sugarcane plants which produce the best growth, 3) To see the results of research on the growth of sugarcane can be used biology learning resources. This type of research is an experimental study using a completely randomized design (CRD). This study consisted of 4 treatments, namely, the first treatment was giving sand and red soil, the second treatment was giving manure and 15% concentration of onion solution phytohormones, the third treatment was giving manure and phytohormones with 25% concentration of coconut water solution, the fourth treatment was Pembrian. Manure and phytohormone combined with 15% concentration of onion solution + phytohormone with 25% concentration of coconut water solution. The parameters observed in this study were height in units (cm), number of leaves (counting manually), stem diameter in units (cm). To determine the effect of phytohormone solutions on shallots and coconut water, data analysis was carried out using the one-way ANOVA test. and further tests to find out the most optimum treatment for the growth of sugarcane using the BNJ test. Based on the research, there was a significant effect of giving natural phytohormones on the growth of sugarcane, with the best treatment, namely the third treatment of giving manure and phytohormones of coconut water solution. The results of this research can be used as a source of learning biology in the form of videos with material on the growth and development of class XII. Kata kunci: larutan bawang merah (allium cepa L), air  kelapa (cocos nucifera L), fitohormon, tanamantebu.